Herschel-ATLAS: modelling the first strong gravitational lenses - Dye, S.; Negrello, M.; Hopwood, R.; Nightingale, J.W.; Bussmann, R.S.; Amber, S.; Bourne, N.; Cooray, A.; Dariush, A.; Dunne, L.; Eales, S.A.; González-Nuevo, J.; et al. (Oxford University Press, 2014)
We have determined the mass density radial profiles of the first five strong gravitational lens systems discovered by the Herschel Astrophysical Terahertz Large Area Survey. We present an enhancement of the semilinear lens inversion method of Warren & Dye which allows simultaneous reconstruction of several different wavebands and apply this to dual-band imaging of the lenses acquired with the Hubble Space Telescope. The five systems analysed here have lens redshifts which span a range 0.22 ≤ z ≤ 0.94. Our findings are consistent with other studies by concluding that: (1) the logarithmic slope of the total mass density profile steepens with decreasing redshift; (2) the slope is positively correlated with the average total projected mass density of the lens contained within half the effective radius and negatively correlated with the effective radius; (3) the fraction of dark matter contained within half the effective radius increases with increasing effective radius and increases with redshift.